Sosialisasi pentingnya vaksinasi terhadap masyarakat sari mulya guna mencegah penularan virus Covid-19 - Muhammad Yogi Riyantama Isjoni; Bela Islami; Rian Saputra; Tubagus Ageng Agagis; Aprilia Nur Hasti; Yulismi Purnama Sari; Resi Sundari; Ratnasari Ratnasari; Elsa Afrianti; Sephia Marsha Tiara Dinda Lofa; Rinda Wulandari (Unri Conference Series: Community Engagement, 2021)
The COVID-19 pandemic has had an impact on all areas of human life. The Indonesian government's efforts to reduce the number of sufferers and transmission of Covid-19 continue to be carried out, one of which is through socialization of Covid-19 prevention. In the midst of the spread of the government's plan for vaccination, various hoaxes have sprung up which are spread by accounts that do not have the knowledge capacity. The understanding of vaccination among villagers is still unclear, so socialization about vaccination is needed. The development of the hoax is very dangerous. As an effort to handle this case, socialization and guidance about the Covid-19 vaccine was carried out to the people of Sari Mulya Village which coincided on July 15, 2021. This socialization was tried directly to the community. The socialization linked the residents of Sari Mulya Village and the Pangkalan Lesung Health Center. This activity was attempted as an effort to help socialize the importance of the Covid-19 vaccination program. The results of this socialization are expected to increase people's knowledge of how important vaccination is to correct lifestyles so that they can return to stability.